Conflict-induced IDPs and the Spread of Conflict. (April 2018) - Bohnet, Heidrun; Cottier, Fabien; Hug, Simon
Recent scholarship has found evidence that refugee flows may inadvertently contribute to the spread of conflict across borders. Little is known, however, about the spatial diffusion of conflict within a state's borders and what role internal displacement plays in such a dynamic. This question is of relevance because of the particular marginalization of internally displaced persons, which make them at risk of predation and militarization by armed groups. Drawing on a novel global data set on internal displacement, we evaluate this question and find evidence for a similar mechanism leading to conflict spread operating at the domestic level.